Pengaruh Faktor Makroekonomi dan Mikroekonomi Terhadap Struktur Modal pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2012-2016 - Yentifa, Armel; Frima, Rini; Novita, Nella (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This research meant to find out the influence of BI interest rates, exchange rates (US dollar exchange rates), profitability, and asset structure to the capital structure. The independent variables in this research are BI interest rates, exchange rates (US dollar exchange rates), profitability, and asset structure. The dependent variable is the capital structure that measured using the debt to equity ratio (DER). Population teken as object obsevation 40 mining companies listed in Indonesia Stock Exchange 2012-2016 period. Determination of sample was made by applying purposive sampling method and obtaining a sample of 15 mining companies. Analysis of data used is multiple regression with the help of SPSS versio 20. The result showed that profitability had negative influence on capital structure, while the BI interest rate and exchange rate (US dollar exchange rate) did not negative influence also the asset structure did not positive influence on capital structure.